Experiences of adolescent lung transplant recipients: A qualitative study. (1st February 2017) - Anderson, S. M.; Wray, J.; Ralph, A.; Spencer, H.; Lunnon‐Wood, T.; Gannon, K.
Abstract: Many young transplant recipients experience psychological distress and adjustment difficulties, yet there is little research investigating lung transplantation from the recipients' perspective. This qualitative study aimed to explore experiences of young people who underwent lung transplantation. Semi‐structured interviews were conducted with six lung transplant recipients (aged 15‐18). Interviews were analysed using IPA, a qualitative research approach examining how people make sense of their major life experiences. The analysis revealed three master themes: "Living with Dodgy Lungs" outlined how participants dealt with their experiences, managing through accepting or discussing their feelings with others, although talking was often difficult. "The Big Deal" reflected participants' experiences of the process, their expectations, and the contrast of their lives pre‐ and post‐transplant. Inherent in their accounts was the profound meaning ascribed to transplantation, the emotional turmoil, and impact on their lives. "A Sense of Self" illustrated participants' developing identities within their social contexts and at times isolating experiences. The results highlight key areas where adolescent lung transplant recipients could be supported by clinicians, enabling the promotion of psychological well‐being. Examples include supporting identity integration post‐transplant, facilitating social inclusion, considering alternative means of support, and involving adolescents in healthcare decisions.